Study on the environmental impact of the El Rejo River Dam on flora and fauna in adjacent ecosystems Cajamarca, Peru - Tenorio-Maluquis, Eyder; Rodriguez-Medina, Nayumi; Torres-Chavez, Diana; Vergara-Arana, Juan; Infante-Luna, Jhon; Culqui-Rabanal, Maria; Sanchez-Peña, Marco (LACCEI, 2025)
This study examines the environmental impact of the El Rejo River artificial dam, located in Cajamarca, Peru, on nearby high Andean ecosystems. Built in 2002 by Yanacocha SRL to control mining sediments and supply water to agriculture during dry seasons, the dam has significantly altered the natural landscape. In 2016, 2018, and 2025, flooding exceeded 8 hectares, intensifying ecological disturbances. The research identified 11 plant species and 6 animal species in the surrounding area. Among the flora are Polylepis weberbaueri and Polylepis racemosa, both considered vulnerable. Fauna includes the endangered monarch butterfly (Danaus plexippus). Prolonged flooding has led to the loss of native vegetation, habitat fragmentation, and the expansion of hydrophilous and invasive species. These changes have altered ecological processes, including natural regeneration. Impacts on birds and small mammals were also observed, particularly due to the alteration of travel routes and nesting areas. To mitigate these effects, the study proposes an ecological restoration strategy: automated water level monitoring, reforestation with native species, regulated ecotourism, and continuous environmental monitoring. These actions seek to promote biodiversity recovery and strengthen ecological resilience. The findings underscore the need for sustainable water infrastructure planning that considers the ecological sensitivity of high-altitude environments.